Experimental Study on Shock Wave Propagation of the Explosion in a Pipe with Holes by High-Speed Schlieren Method - Gang Zhang (Shock and Vibration)
The shock wave propagation of the explosion in a pipe with holes was studied by a high-speed schlieren experimental system. In the experiments, schlieren images in the explosion were recorded by a high-speed camera from parallel and perpendicular orientations, respectively, and the pressure in the air was measured by an overpressure test system. In parallel orientation, it is observed that the steel pipe blocks the propagation of blast gases, but it allows the propagation of shock waves with a symmetrical shape. In perpendicular orientation, oblique shock wave fronts were observed, indicating the propagation of explosion detonation along the charge. Shock wave velocity in the hole direction is larger than that in the nonhole direction, indicating the function of holes in controlling blast energy, that is, leading blast energy to hole direction. Furthermore, the function of holes is verified by overpressure measurements in which peak overpressure in the hole direction is 0.87 KPa, 2.8 times larger than that in the nonhole direction. Finally, the variation of pressure around the explosion in a pipe with holes was analyzed by numerical simulation, qualitatively agreeing with high-speed schlieren experiments.